Exploring the Phenotypic Profile of Acute Flaccid Paralysis: Insights from a Third-Level Pediatric Emergency Room - Hosseinpour, Sareh; Pazouki, Roxana; Ashrafi, Mahmoud Reza; Bemanalizadeh, Maryam; Ghahvechi Akbari, Masood; Rezaei, Sanaz; Parvaneh, Nima; Heidari, Morteza; Vafaee-Shahi, Mohammad; Hosseini, Firouzeh; et al. (Iranian Journal of Child Neurology, 2024)
Objectives Acute Flaccid Paralysis (AFP) in children can stem from a diverse array of potential diagnoses. Materials & Methods This retrospective study sought to diagnose children referred to a referral pediatric emergency unit with AFP between 2011 and 2016. The study gathered clinical observations, conducted stool and cerebrospinal fluid analyses, and assessed electrophysiological and imaging data. Results The present study enrolled 118 fully immunized children with a mean age of 6.09 ± 3.60 years. The most prevalent diagnoses included Guillain-Barré Syndrome (GBS-80 cases), acute viral myositis (20 cases), Transverse Myelitis Syndrome (TMS) (TMS-6 cases), and Vaccine-Associated Paralytic Poliomyelitis (VAPP) (VAPP-6 cases). All these six patients had primary immunodeficiency. Notably, all patients tested negative for poliovirus in stool analyses. This study encountered a unique case of a 2.5-monthold male patient who presented with acute limb motor weakness, along with fever, irritability, new-onset hypotonia, and generalized decreased deep tendon reflexes. Notably, no signs of upper motor neuron involvement were found. The Cerebrospinal Fluid (CSF) analysis was compatible with the diagnosis of viral meningitis. Moreover, among the 60 brain and spinal imaging series performed, five were indicative of GBS, six cases showed evidence of TMS, and one revealed a spinal mass. Besides, clinical investigations pointed toward acute viral myositis as a secondary etiology of AFP in 20 patients in this study. Conclusion In this hospital-based study, the most frequent diagnoses for children arriving at a third-level pediatric Emergency Room (ER) with acute flaccid paralysis AFP were GBS, acute viral myositis, TMS, and VAPP). These findings suggest a distinct pattern of AFP causes compared to those found in community-based epidemiological studies. Additionally, notably, unusual conditions, such as viral meningitis, can rarely present with AFP-like symptoms. Assessment for primary immune deficiency should be considered in cases of VAPP. Lastly, this research has implemented a pediatric AFP Management Protocol: A Local Practical Approach